Endocytotic Formation of Vesicles and Other Membranous Structures Induced by Ca(2+) and Axolemmal Injury - Eddleman, Christopher S. (J Neurosci, 1998)
Vesicles and/or other membranous structures that form after axolemmal damage have recently been shown to repair (seal) the axolemma of various nerve axons. To determine the origin of such membranous structures, (1) we internally dialyzed isolated intact squid giant axons (GAs) and showed that elevation of intracellular Ca(2+) >100 μm produced membranous structures similar to those in axons transected in Ca(2+)-containing physiological saline; (2) we exposed GA axoplasm to Ca(2+)-containing salines and observed that membranous structures did not form after removing the axolemma and glial sheath but did form in severed GAs after >99% of their axoplasm was removed by internal perfusion; (3) we examined transected GAs and crayfish medial giant axons (MGAs) with time-lapse confocal fluorescence microscopy and showed that many injury-induced vesicles formed by endocytosis of the axolemma; (4) we examined the cut ends of GAs and MGAs with electron microscopy and showed that most membranous structures were single-walled at short (5–15 min) post-transection times, whereas more were double- and multi-walled and of probable glial origin after longer (30–150 min) post-transection times; and (5) we examined differential interference contrast and confocal images and showed that large and small lesions evoked similar injury responses in which barriers to dye diffusion formed amid an accumulation of vesicles and other membranous structures. These and other data suggest that Ca(2+) inflow at large or small axolemmal lesions induces various membranous structures (including endocytotic vesicles) of glial or axonal origin to form, accumulate, and interact with each other, preformed vesicles, and/or the axolemma to repair the axolemmal damage.